Mechanical properties of cortical fixators for anterior cruciate ligament reconstruction - Krasnoperov, Sergiy; Golovakha, Maksim; Shalomeev, Vadim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Reconstruction of the damaged anterior crucial ligament today is a routine surgery. Violation of graft fixation and its extension are the most frequent causes of instability. Recently acquired cortical use button latches become popular. Objective: to evaluate the possibility of using own cortical locking fixation with adaptive loop based on the study of its mechanical characteristics. Methods: using the bursting of hydraulic machines tested two types of clamps with cortical adaptive loop: 1) TightRope anterior crucial ligament (Arthrex Inc., Naples, FL) eg reverse thrust; 2) own, consisting of button plate and thread Fiberwire № 2 (Arthrex Inc., Naples, FL). To determineload extension have made constant load of 50 H for 30 s. Next applied given sinusoidal cyclic preloading from 50 to 250 H with a frequency of 2 Hz. Repeat exertion after 50, 100, 500, 1 000 and 2 000 cycles of loading has been assessed. Stretched loop extension of 1 mm/s to determine the maximum tensile strength. Results: the mean values of load extension did not differ (p > 0.05) in cortical locking own making ((2.07 ± 0.3) mm) and commercially available ((1.95 ± 0.2) mm). The difference between the total cyclic extension after 2000 loading cycles was also statistically significant — (1.1 ± 0.1) mm and factory (1.21 ± 0.13) mm in copyright holder. there is no difference overall in elongation (perednavantazhenoho and cyclic) — (3.05 ± 0.95) mm of plant holder, (3.28 ± 0.22) mm in own fixation device; maximum tensile strength — (876 ± 56) and (953 ± 48) H respectively. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> yielded similar mechanical characteristics of the studied devices such as sufficient tensile strength and elongation opportunity, allow us to recommend them for use in reconstructive surgery of anterior crucial ligament.